Haunting the Ganges: addressing the issues of ghost gear in the Ganga River through an incentive-based institutional mechanism - Badola, Srishti; Gill, Amanat Kaur; Dobriyal, Pariva; Patel, Surshti; Khan, Mohd. Zayed; Hussain, Syed Ainul (Frontiers in Conservation Science, 2024)
Abandoned, lost, or otherwise discarded fishing gears, also known as ghost gears (GG), are major contributors to global marine and freshwater plastic pollution. Such GG can lead to the accidental entanglement of several threatened freshwater and marine species, especially the air-breathing aquatic vertebrates, which is a matter of global concern. There is a lack of knowhow and mechanisms for collecting and recycling such GG, leading to their constant accumulation in aquatic ecosystems. In this study, we have examined the mortalities of threatened aquatic species in fishing nets and have proposed an incentive-based standard operating procedure (SOP) for effective collection and disposal of GG based on field observations and extant national and international policies and made recommendations for a net buyback scheme as a possible downstream solution to reduce GG in the Ganga River Basin.It is proposed that the collection of GG can be done by the local level institutions of fishing community through the fair-price shops. The nets are then to be deposited at the block-level processing centres to be transported to the district-level consolidating centres. Recycling partners identified by the Government of India will then collect the nets directly from district centres for further upcycling and recycling. A multi-level, multi-stakeholder approach with strong upstream and downstream linkages backed with appropriate policy interventions is needed to tackle the ghost gear issue in the Ganga River basin.